Midwives’ Knowledge and Readiness to Practice Antenatal Screening and Genetic Testing in selected Hospitals in Lagos, Nigeria (2021)
Background & aim: The burden of congenital malformation can be decreased through two major approaches‐ primary prevention of those at risk through antenatal screening and improving survival for those affected. This study was conducted to investigate the knowledge and readiness of midwives to practice antenatal screening and genetic testing for congenital abnormalities. Methods: A cross‐sectional study among randomly selected 245 midwives across five maternal and child health government hospitals within Lagos metropolis in 2017. The validated self‐administered questionnaire having 3‐section; midwife’s demographic‐characteristics, knowledge and readiness of antenatal screening and genetic testing, with 0.74 reliability coefficient, was used to obtain information within five weeks after obtaining ethical approval. The obtained information was analysed using SPSS version 22. Results: The study findings revealed that 62.9% of the midwives had inadequate knowledge of antenatal screening and genetic testing for congenital abnormalities. Up to 82.4% were ready to practice antenatal screening and genetic testing for congenital abnormalities. The midwives’ level of knowledge was not significantly associated with their readiness to practice antenatal screening and genetic testing for congenital abnormalities (p=0.74), meanwhile, professional qualification (p = 0.003) and years of experience (p < 0.001) were significantly associated with readiness to practice antenatal screening and genetic testing. Conclusion: The study recommends that midwives should improve their knowledge and skills in genetic testing by attending both local and international training workshops/seminars. Midwives should be provided with the screening devices to facilitate the practice of antenatal screening and genetic testing for congenital abnormalities.